Deformation of the Cape Chignecto Pluton, Cobequid Highlands, Nova Scotia: thrusting at the Meguma-Avalon boundary - Waldron, John W.F.; Piper, J. W.; Pe-Piper, Georgia (Atlantic Geoscience, 1989)
The Early Carboniferous Cape Chignecto pluton, at the western end of the Cobequid Highlands in the Avalon Terrane of Nova Scotia, consists predominantly of two-feldspar biotite granite. Intrusion of smaller diorite bodies locally melted and hybridized the granite. Diabase and microgranite dykes cut the plutons. Much of the pluton has a flat-lying mylonitic foliation, with a mineral elongation lineation trending between north and west. Quartz is dynamically recrystallized, but feldspars show predominantly brittle deformation. The phiton was probably deformed under greenschist facies conditions, after cooling. C-S fabrics observed in the field, and tails on porphyroclasts seen in thin section, indicate northward overthrusting. The Hadrynian Jeffers Group is thrust over the south edge of the phiton in the Fowler Brook inlier. At its north edge, the pluton is probably thrust over volcanic rocks of die Fountain Lake Group. The deformation of the pluton is constrained by stratigraphic relationships and isotopic dates to a Namurian or possibly early Westphalian age. Deformation within the pluton is correlated with Namurian uplift of the Cobequid and Caledonia Highlands. It records either transpression resulting from the curvature of the Meguma-Avalon boundary or a major component of convergent movement between the Meguma and Avalon terranes. RÉSUMÉ Le pluton de Cape Chignecto, daté du début du Carbonifere et situé à l’extremité occidentale des Monts Cobequid (Lanière d’Avalon, Nouvelle-Écosse), est formé en majeure partie de granite à biotite à deux feldspaths. Le granite subit une fonte et une hybridation locales lore de l’ intrusion de batis dioritiques de plus faibles dimensions. Des dykes de diabase et de microgranite recoupent les plutons. La majeure partie du pluton présente une foliation mylonitique horizontale, avec une linétion d’éirement orientée entre le nord et l’ouesL On note une recristallisation dynamique du quartz mais la déformation des feldspaths est surtout fragile. Le pluton fut probablement déformé sous des conditions appartenant au faciès des schistes verts, et ce après son refroidissement. Des fabriques planaires C-S, observées sur le terrain, et des ombres de pression dissymdtriques, vues en lame mince, indiquent un charriage vers le nord. Le Groupe hadrynien de Jeffers chevauche l’extrémité méridionale du pluton dans la fenetre de Fowler Brook. A son extrémité septentrionale, le pluton chevauche probablement les volcanites du Groupe de Fountain Lake. Les relations stratigraphiqueset des datations radiométriques limitent l’âge de la déformation du pluton au Namurien ou possiblement au début du Westphalien. On corrèle la déformation au sein du pluton avec la surrection namurienne des monts Cobequid et Caledonia. Cette déformation enregistre soil une transpression résultant de la cambrure de la jonction Meguma-Avalon, soil une forte composanle de mouvement convergent entre les lanières de Meguma et d* Avalon. [Traduit par le journal]